Continuum of maternity care in Zambia: a national representative survey - Quraish Sserwanja; Milton W. Musaba; Linet M. Mutisya; Emmanuel Olal; David Mukunya (BMC Pregnancy and Childbirth, 2021)
Abstract Background Globally, over half of maternal deaths are related to pregnancy-related complications. Provision of a continuum of care during pregnancy, childbirth and the postnatal period results in reduced maternal and neonatal morbidity and mortality. Hence this study determined the prevalence of the continuum of care and its determinants among women in Zambia. Methods We used weighted data from the Zambian Demographic and Health Survey (ZDHS) of 2018 for 7325 women aged 15 to 49 years. Multistage stratified sampling was used to select study participants. Complete continuum of care was considered when a woman had; at least four antenatal care (ANC) contacts, utilized a health facility for childbirth and had at least one postnatal check-up within six weeks. We conducted multivariable logistic regression to explore continuum of care in Zambia. All our analyses were done using SPSS version 25. Results Of the 7,325 women, 38.0% (2787/7325) (95% confidence interval (CI): 36.9-39.1) had complete continuum of maternal healthcare. Women who had attained tertiary level of education (adjusted odds ratio (AOR): 1.93, 95% CI: 1.09-3.42) and whose partners had also attained tertiary level of education (AOR: 2.58, 95% CI: 1.54-4.32) were more likely to utilize the whole continuum of care compared to those who had no education. Women who initiated ANC after the first trimester (AOR: 0.46, 95% CI: 0.39-0.53) were less likely to utilize the whole continuum of care compared to those who initiated in the first semester. Women with exposure to radio (AOR: 1.58, 95% CI: 1.27-1.96) were more likely to utilize the whole continuum of care compared to those who were not exposed to radio. Women residing in the Western province were less likely to utilize the entire continuum of care compared to those in the other nine provinces. Conclusion Level of education of the women and of their partners, early timing of ANC initiation, residing in other provinces other than the Western province, and exposure to information through radio were positively associated with utilization of the entire continuum of care. Improving literacy levels and promoting maternity services through radio may improve the level of utilization of maternity services.